Empowering health volunteer's through participatory action research in a comprehensive healthcare center - Fatemeh Vizeshfar; Marzieh Momennasab; Shahrzad Yektatalab; Mohamad Taghi Iman (BMC, 2021)
Abstract Background Health volunteers act as the link between the society and the healthcare system and are a symbol of people's participation in the health maintenance and promotion. Despite the important role of health volunteers in the health system, it seems that they experience several problems. The aim of this study was empowering health volunteers through an action research. Methods This participatory action research was conducted through two continuous cycles of reflection and acting for change over 20 months, in a comprehensive health center in Southern of Fars province in Iran. Participants included 25 health volunteers; two instructors and an academic researcher as facilitator. In the first cycle the participants discovered the challenges of health volunteers, prioritized them, designed an action plan, and implemented it. At the end of this cycle, evaluation was done with the participants' cooperation. The second cycle began with reflecting on the results of the first cycle and then after designing and implementing second action plan, final evaluation was done. Results Qualitative content analysis in the first phase led to the emergence of four categories, including role confusion, inadequate volunteer training, deficits in attracting and keeping volunteers, and being unfamiliar to the public. After the implementation of the action plan the participants learned through reflection and immersing in action. Finally, quantitative and qualitative data showed improvement of knowledge and performance, satisfaction, effectiveness of programs and improvement in volunteer's competence. Conclusions Clarification of volunteers' roles, supporting volunteers to improve their knowledge and skills with coherent planning based on their educational needs, are appropriate management plans to attract and retain volunteers. By presenting their services to the society, they will be empowered and motivated to continue.